Enhanced visible-light-driven photocatalytic activity of B-doped BiVO4 synthesized using a corn stem template. (February 2015) - Wang, Min; Zheng, Haoyan; Liu, Jun; Dong, Duo; Che, Yinsheng; Yang, Changxiu
Abstract: Through a combination of template and sol-gel methods, B-doped Corn stem-BiVO4 (CS-BiVO4 ) photocatalysts were prepared using CS as a template. The synthesized materials were characterized by XPS, XRD, SEM, BET, and UV–vis DRS. The photocatalytic performances of the BiVO4 samples were evaluated during the degradation of methyl orange under visible light irradiation. Compared to the undoped CS-BiVO4 sample, the B-doped CS-BiVO4 samples retained their monoclinic structure while exhibiting higher surface areas, greater V 4+ densities and lower band gap energies. Among the prepared samples, 0.04B CS-BiVO4 exhibited the best photocatalytic performance during the photodegradation of MO. The apparent difference in photocatalytic activity between 0.04B CS-BiVO4 and 0.04B-BiVO4 may be attributed to the cellular morphology from the CS and the higher specific surface areas.